Effect of grain mass properties on the processes of extraction and hydration - Yanyuk, Tatiana; Trakalo, Tetiana; Liashko, Halyna; Galynska, Olena; Hriunvald, Nataliia (My University, 2021)
Introduction. The aim of the present research was to determine the quantity of non-freezing water in the mixtures of flax seeds where carbohydrates are mainly heteropolysaccharides and in amaranth, oats and rice mixtures where carbohydrates are mainly monopolysaccharides. Materials and methods. Water and whey were chosen as solvents. Extracts were prepared by solvent addition to hydrated raw materials with a moisture content, %: flax seeds, 6.3; amaranth seeds, 9.4; oats. 10.5, and rice, 11.8. The state of water in the mixtures at different stages of hydration was studied by the method of low-temperature canning calorimetry. Вступ. Метою цього дослідження було визначити кількість незамерзаючої води в сумішах насіння льону, де вуглеводи є переважно гетерополісахаридами, та в сумішах амаранту, вівса та рису, де вуглеводи є переважно монополісахаридами. Матеріали та методи. Як розчинники були обрані вода та сироватка. Екстракти готували шляхом додавання розчинника до гідратованої сировини з вмістом вологи, %: насіння льону – 6,3; насіння амаранту – 9,4; овес – 10,5 та рис – 11,8. Стан води в сумішах на різних стадіях гідратації вивчали методом низькотемпературної консервної калориметрії.
Keywords: кафедра технології зберігання і переробки зерна; grinding; grain; hydration; extraction; hydromodul; зерно; гідратація; екстракція; гідромодуль; подрібнення